Diverse landscapes beneath Pine Island Glacier influence ice flow. Issue 1 (December 2017) - Bingham, Robert; Vaughan, David; King, Edward; Davies, Damon; Cornford, Stephen; Smith, Andrew; Arthern, Robert; Brisbourne, Alex; Rydt, Jan; Graham, Alastair; Spagnolo, Matteo; Marsh, Oliver; et al.
Abstract The retreating Pine Island Glacier (PIG), West Antarctica, presently contributes 5–10% of global sea-level rise. PIG's retreat rate has increased in recent decades with associated thinning migrating upstream into tributaries feeding the main glacier trunk. To project future change requires modelling that includes robust parameterisation of basal traction, the resistance to ice flow at the bed. However, most ice-sheet models estimate basal traction from satellite-derived surface velocity, without a priori knowledge of the key processes from which it is derived, namely friction at the ice-bed interface and form drag, and the resistance to ice flow that arises as ice deforms to negotiate bed topography. Here, we present high-resolution maps, acquired using ice-penetrating radar, of the bed topography across parts of PIG. Contrary to lower-resolution data currently used for ice-sheet models, these data show a contrasting topography across the ice-bed interface. We show that these diverse subglacial landscapes have an impact on ice flow, and present a challenge for modelling ice-sheet evolution and projecting global sea-level rise from ice-sheet loss. Projecting the future retreat and thus global sea level contributions of Antarctica's Pine Island Glacier is hampered by a poor grasp of what controls flow at the ice base. Here, via high-resolution ice-radar imaging, the authors show diverse landscapes beneath the glacier fundamentally influence ice flow.